Roughness and color evaluation of wood polymer composites filled by household waste of mate-tea - H. G. de Cademartori, Pedro; L. Missio, André; D. Mattos, Bruno; A. Gatto, Darci; L. E. Magalhães, Washington; A. Lima, Edson (Maderas. Ciencia y Tecnología, 2025)
This study presents the preparation of polypropylene composites filled with mixtures of household waste of mate-tea and wood particles to increase the economic value chain of mate-tea, especially in Latin America. Filler mixtures in proportions ranging from 0 to 60% depending on the type of particle were used. The polypropylene matrix was fixed at 40% and roughness surface and color evaluation were performed. The highest mean roughness (Ra) was observed for the composite with 30:30% proportion of filler mixture, which denotes the difficulty of homogenizing a mixture of fillers with different shapes and dimensions. Nevertheless, even with higher roughness for composites with a balanced blend of filler, this does not imply the presence of large peaks and valleys. In general, all the composites presented a dark color. Variation of color composites was more evident for higher proportions of household waste of mate-tea.